2014
DOI: 10.1136/bmj.g5243
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of routine antenatal determination of fetal RHD status across gestation: population based cohort study

Abstract: Objectives To assess the accuracy of fetal RHD genotyping using cell-free fetal DNA in maternal plasma at different gestational ages.Design A prospective multicentre cohort study. Setting Seven maternity units in England.Participants RhD negative pregnant women who booked for antenatal care before 24 weeks' gestation.Interventions Women who gave consent for fetal RHD genotyping had blood taken at the time of booking for antenatal care and, when possible, at other routine visits such as for Down's syndrome scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 14 publications
(20 reference statements)
0
100
0
Order By: Relevance
“…All the studies were prospective studies and were conducted in European countries. Four studies were conducted in England,12,[17][18][19] three of which were based in Bristol. 12,17,18 The sample size (number of patients/samples analysed) of studies ranged from 282 to 18,383 …”
Section: Results: Assessment Of Diagnostic Accuracymentioning
confidence: 99%
See 4 more Smart Citations
“…All the studies were prospective studies and were conducted in European countries. Four studies were conducted in England,12,[17][18][19] three of which were based in Bristol. 12,17,18 The sample size (number of patients/samples analysed) of studies ranged from 282 to 18,383 …”
Section: Results: Assessment Of Diagnostic Accuracymentioning
confidence: 99%
“…Only three studies stated that their diagnostic threshold was prespecified during the conduct of the screening programme. 12,17,20 None of the studies reported whether or not there were any adverse events from the index test or reference standard. Two studies 19,21 were judged as having a high risk of bias.…”
Section: Risk Of Bias Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations